The Effect of Empowerment Program on Quality of Life in Older Adults with Stage 3 Chronic Kidney Disease - Faramee, Kanthima; Kaewkerd , Onuma; Wuttiso, Paitoon (Journal of The Royal Thai Army Nurses, 2024)
This research is quasi-experimental. The objective is to study and compare the results of the empowerment program on the quality of life of elderly people with stage 3 chronic kidney failure. The sample group was Sixty-eight elderly people with stage 3 chronic kidney failure were selected by purposive methods. Divided into an experimental group and a control group, 34 people per group. Research tools include a Personal information questionnaire Thai version of the preliminary brain condition test (IOC = 1.00) Knowledge assessment of chronic kidney disease (IOC = 1.00) Empowerment assessment form the SF-36 quality of life assessment has Cronbach’s alpha coefficient of 0.93, 0.95, respectively. Data were analyzed using descriptive statistics by distribution, frequency, percentage, mean, and deviation. Standardize analyze and compare general information of both sample groups using an Independent Samples t-test, Dependent Group, or Paired Samples t-test. The research results found that: the experimental group had averages of empowerment, quality of life, and knowledge about kidney disease. Before and after the experiment were significantly different at the .001 level. The control group was not different. and comparison between the experimental group and the control group. After the experiment, there was an average Empowerment, quality of life, and knowledge about kidney disease The difference is statistically significant at the .001 level. Research results can be used as nursing guidelines to further improve the quality of life of elderly patients.